Principles - Ray Dalio (New York Simon & Schuster, 2017)
Principles: Life & Work is a 2017 book by hedge fund manager Ray Dalio based on principles he had developed while leading Bridgewater Associates. These Principles for Success were also made available as an ultra mini-series adventure by the author.
Keywords: Dalio, Ray, 1949-